Factors influencing student enrollment decision in selection of higher education institutions (HEIS) / Siti Nuryiana Sidik - Sidik, Siti Nuryiana (2014)
Higher education environments have become increasingly competitive and higher educational institutions also have increased substantially. However, the higher education institutions (HEIs) are faced with a difficult situation of trying to understand how students select HEIs of their choice. This study is aimed to identify the variables related to the choice criteria of factors that affect students’ choices of HEIs and also to investigate the factors that have the greatest influence on students’ choice in the selection of HEIs. Findings of this study will be beneficial to assist the HEIs marketer to plan and improve their approach to attract and enroll students.